Electrical Injury-Induced New Onset Dysautonomia - Singh, Harinder R.; Gowda, Srinath (Journal of Pediatric Neurology, 2015)
We report a young athletic man with low voltage electrical injury that led to progressively worsening symptomatology of autonomic dysfunction including easy fatigability, weakness, palpitations, chest discomfort, and dizziness. Other potential causes for his symptomatology were ruled out. Disopyramide was initiated targeting his autonomic response to orthostatic changes with successful alleviation of his symptoms.
Keywords: electrical injury; dysautonomia; disopyramide